2022
DOI: 10.30650/ajte.v4i1.3224
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading Comprehension Through Genre-Based Approach (GBA) at Senior High School

Abstract: This research is about teaching reading comprehension through a genre-based approach (GBA) at senior high school. The study aimed to increase students' reading comprehension in the eighth grade at SMP Negeri 1 Sibulue through the Genre-Based Approach (GBA). This research used Classroom Action Research (CAR) that consisted of two cycles. The research subject was the eighth grade of SMP Negeri 1 Sibulue academic year 2021/2022 that consisting of 25 students. The researcher obtained the data by using a reading te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…Therefore, when implementing the 2013 curriculum, the students' reading literacy scored low in PISA 2015 -2018, and so will the next PISA test. This result is in line with several studies related to the use of genre-based approach for teaching reading which found that the genre-based approach can increase reading comprehension (Fitrawati, 2012;Gunawan, 2022;Montero-Arévalo, 2019;Muh. Said & Munawir, 2022;Nabella & Rini, 2023), yet, reading literacy is not about comprehension only but also how the comprehension from reading is used for various life purposes, dealing with text.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, when implementing the 2013 curriculum, the students' reading literacy scored low in PISA 2015 -2018, and so will the next PISA test. This result is in line with several studies related to the use of genre-based approach for teaching reading which found that the genre-based approach can increase reading comprehension (Fitrawati, 2012;Gunawan, 2022;Montero-Arévalo, 2019;Muh. Said & Munawir, 2022;Nabella & Rini, 2023), yet, reading literacy is not about comprehension only but also how the comprehension from reading is used for various life purposes, dealing with text.…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned by Styati & Khasanah (2022), reading activity needs a strategy and media to help the students understand the meaning of words in the text The second problem is motivation. Students' lack of motivation can cause lack of interest in reading so that it fosters a sense of laziness (Gunawan, 2022). The third problem has become one of background knowledge.…”
Section: Introductionmentioning
confidence: 99%